Attachment Style Profiles Across Depression Levels among Undergraduate Students: A Descriptive Study - Pupung Sugitri; Susi Fitri (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
This study aims to describe attachment style profiles based on depression levels among undergraduate students in the Faculty of Education, Universitas Negeri Jakarta. A descriptive quantitative design was employed. The respondents consisted of 738 students from the 2016, 2017, and 2018 cohorts, selected using proportional stratified random sampling. Data were collected using the Adult Attachment Scale (AAS) and the Beck Depression Inventory (BDI). The AAS classified students into secure, avoidant, anxious/ambivalent, and combined attachment categories, while the BDI classified depression levels. Data were analysed using descriptive statistics, including frequencies, percentages, and cross-tabulations. The findings show that secure attachment was the dominant profile across the three cohorts. Most students were categorized within normal mood fluctuation and mild mood disturbance levels, although smaller proportions were found in borderline clinical depression, moderate depression, severe depression, and extreme depression categories. These findings provide an initial profile of students’ attachment and depression patterns and highlight the need for preventive mental health support in higher education.